2009
DOI: 10.1128/jvi.00355-09
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Pathologic Roles of the Immune Response to Mouse Hepatitis Virus Type 1: Implications for Severe Acute Respiratory Syndrome

Abstract: Intranasal mouse hepatitis virus type 1 (MHV-1) infection of mice induces lung pathology similar to that observed in severe acute respiratory syndrome (SARS) patients. However, the severity of MHV-1-induced pulmonary disease varies among mouse strains, and it has been suggested that differences in the host immune response might account for this variation. It has also been suggested that immunopathology may represent an important clinical feature of SARS. Little is known about the host immune response to MHV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(93 citation statements)
references
References 89 publications
7
86
0
Order By: Relevance
“…Interestingly, infection by MHV 2 days prior to PR8 also reduced the severity of PR8 infection. Unlike RV, MHV causes morbidity and mortality in mice, though virulence depends on the mouse strain (30,31,59). We have observed dose-dependent severity of MHV in BALB/c mice.…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, infection by MHV 2 days prior to PR8 also reduced the severity of PR8 infection. Unlike RV, MHV causes morbidity and mortality in mice, though virulence depends on the mouse strain (30,31,59). We have observed dose-dependent severity of MHV in BALB/c mice.…”
Section: Discussionmentioning
confidence: 69%
“…In the preliminary experiments, a subjective mouse wellness score (25) was worse in the first 2 days for the LPS groups, but was essentially the same for all groups from day 4 to day 7 (data not shown). Additionally, although the mice lost weight over the first 48 -72 h, by the end of the observation period Measurements performed at time of harvest (48 h) demonstrate that creatinine was significantly higher in both AKI groups vs. respective controls (PBS and LPS).…”
Section: Expression Of Mcp-1 Increases In Aki and Alimentioning
confidence: 83%
“…Subsequent publications have confirmed that variable sensitivity to MHV-1 infection is a consequence of the innate and adaptive immune responses (Khanolkar et al, 2009a) and that MHV infection inhibits IFN production (Zhou and Perlman, 2007). Notably, MHV-1-specific T and B cell responses exert protective effects that minimize morbidity in C57Bl/6 mice (Khanolkar et al, 2009a). Given the contribution of innate and adaptive immune responses to morbidity in MHV-1 infection of C57Bl/6 mice and the accumulating data that WAP proteins influence susceptibility to infection, employing ps20 +/+ and ps20 À/À C57Bl/6 mice we examined the effects of ps20 on the immune response to MHV-1 infection.…”
Section: Introductionmentioning
confidence: 92%
“…A/J mice are more susceptible to MHV-1 infection compared to C57Bl/6 mice (Albuquerque et al, 2006;Khanolkar et al, 2009a). To assess the role of ps20 in MHV-1 infection of A/J mice, mice were pre-treated with the anti-ps20 FAb fragmented antibody IG7 at either 2 or 6 h prior to MHV-1 infection.…”
Section: Ps20 Confers Protection From Mhv-1 Infection In Vivomentioning
confidence: 99%
See 1 more Smart Citation